Remarks About Targeted Killing in the Light of Public International Law - Łaski, Piotr (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The premises concerning the use of force are currently changing, as are the goals and methods, which entails that appropriate adaptation and interpretation of international legal norms is required in the context of new threats and methods of combating them. This constitutes a significant problem, especially in the event of extraordinary circumstances that are to justify the use of unilateral measures without the consent of the UN Security Council. This encompasses, inter alia, the issue of targeted killing, i.e. eliminating in the territory of another state, while not operating against such a state, on the order of a specific government, a specific person responsible for the illegal use of force, if other methods of apprehending the perpetrator are unrealistic. This makes such a method, in a given circumstance, a legal form of combat, as long as the criterion of necessity and proportionality is taken into account.